Complication of Post Catheterization Transradial Artery: A 24-Month Retrospective Study - Cheyjarean, Nngnapas; Wichienwan, Sireetorn; Chintapanyakun, Teepatad; Meemook, Krissada (Journal of The Royal Thai Army Nurses, 2025)
This retrospective study aimed to compare the complications after catheterization transradial artery the duration of the wrist brace from 4 hours to 2 hours. The sample consisted of 1,013 patients who underwent catheterization transradial artery at the post cardiac care unit, Ramathibodi hospital. The sample was purposively selected. The research instruments were a general information record form, treatment information, and complication information of patients after catheterization transradial artery. The data were analyzed using descriptive statistics and the chi-square test. The results of the research found that the complications of patients after the coronary catheterization procedure through the wrist artery before, during, and after the wrist strap were 1.18, 1.28, and 3.46 percent, respectively. The duration of the wrist strap after the procedure was significantly related to the occurrence of complications of patients after the coronary catheterization procedure through the wrist artery at a statistical level of .05. The occurrence of complications in the group of patients who took 4 hours to loosen the wrist strap after the procedure was higher than the group of patients who took 2 hours to loosen the wrist strap, both before, during, and after the wrist strap was loosened.